Baguettes in Paris by Paris Baguette - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
South Korea’s biggest bakery chain officially makes a classic French food item better than the French; the U.S. and parts of Asia already know that. Is the rest of Europe about to find out?